A Case for Greater Risk Tolerance in Internet Use by Adults with Intellectual Disabilities: A Comment on Chalghoumi et al. Issue 3 (3rd April 2019) - Wasserman, David
Abstract : This comment argues for increased tolerance of privacy risks in the Internet activity of adults with intellectual disabilities. Excessive caution about such risks denies those individuals not only the great benefits of Internet use but also the difficult but valuable experiences of loss, disappointment, and hurt associated with those risks. A level of risk-aversion appropriate for small children will be disrespectful for adults with intellectual disabilities. To the extent that additional safeguards are justified, they are better achieved through individualized security and privacy settings than through caregiver oversight.